Use of alkylated, amphiphilic zinc porphyrins to disperse individualized SWCNTs - Münich, Peter Wilhelm; Wagner, Pawel; Officer, David L.; Guldi, Dirk Michael (Journal of Porphyrins and Phthalocyanines, 2018)
A series of zinc porphyrins, namely ZnPa and ZnPb, which exist predominantly as aggregates, are utilized in a top-down preparation of individualized and stabilized single wall carbon nanotubes (SWCNTs). Sizable interactions in the ground state of the corresponding SWCNT/ZnPa and SWCNT/ZnPb electron donor-acceptor systems lead to charge transfer in the excited state. The product includes the simultaneous reduction of the electron-accepting SWCNTs and the oxidation of the electron-donating ZnPa and ZnPb.
CRIS-Team Scopus Importer:2022-04-14
Keywords: porphyrin; single wall carbon nanotube; spectroscopy